Changes in the level of development of urban and rural communes in the Świętokrzyskie Province - Karpińska, Urszula (Zmiany poziomu rozwoju gmin miejsko-wiejskich w województwie świętokrzyskim, 2019)
Local development is a process of interrelated economic, social, political or cultural changes taking place in the local socio-territorial system. The aim of the article is to assess the level of development of urban-rural communes and determine its spatial diversity using a synthetic measure. Data from the Local Data Bank of the Central Statistical Office for 2012, 2014 and 2017 were used as the source material. The development of the commune is consists of many events and processes belonging to various areas of life of the local community. The problem of development is important in the context of small areas and communities such as the urban-rural commune. The best urban-rural communes in Świętokrzyskie Province, regardless of the method of determining the synthetic measure, are: Połaniec, Daleszyce, Morawica, Busko-Zdrój, and Końskie. Their position was shaped by: the number of employees, of business entities, of natural persons conducting economic activity and financial situation
Biblioteka Regionalisty, 2019, Nr 19, s. 76-88
Keywords: Dolny Śląsk